2018
DOI: 10.3906/sag-1803-183
|View full text |Cite
|
Sign up to set email alerts
|

Hand functions in systemic lupus erythematosus: a comparative study with rheumatoid arthritis patients and healthy subjects

Abstract: Similar to patients with RA, hand functions are significantly impaired in patients with SLE in daily activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Balsamo et al [ 17 ] demonstrated lower dynamic muscle strength along with increased fatigue, reduced functional performance and poorer quality of life in 25 premenopausal SLE patients with low disease activity vs 25 controls matched for age, physical characteristics and the level of physical activity. Bağlan Yentür et al [ 14 ] showed worse hand function in 46 SLE patients (all female) vs 46 healthy controls, but better in comparison to 51 RA patients. All these studies had a smaller sample size than the present study, and none evaluated any potential associations between hand function parameters and disease-related characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Balsamo et al [ 17 ] demonstrated lower dynamic muscle strength along with increased fatigue, reduced functional performance and poorer quality of life in 25 premenopausal SLE patients with low disease activity vs 25 controls matched for age, physical characteristics and the level of physical activity. Bağlan Yentür et al [ 14 ] showed worse hand function in 46 SLE patients (all female) vs 46 healthy controls, but better in comparison to 51 RA patients. All these studies had a smaller sample size than the present study, and none evaluated any potential associations between hand function parameters and disease-related characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a limited number of studies have assessed the hand function and performance of daily activities in SLE patients compared with healthy controls [ 13 , 14 ], and only sporadic studies [ 15–17 ] have examined the impact of demographic and disease-related characteristics on hand function abnormalities. We hypothesized that SLE patients present impaired hand function and difficulties in performance of ADLs, even those with low disease activity.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with a significant impact on function, activities of daily living, work ability and patients’ quality of life 1–5. It has been well documented that upper limb exercise is beneficial to patients with rheumatic disorders such as rheumatoid arthritis,6 7 psoriatic arthritis8 and osteoarthritis 9.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic lupus erythematosus, a rheumatic disease, frequently affects the small joints of the wrist and hands. 1,2 Arthropathy of the hands in systemic lupus erythematosus reduces the ability of twothirds of individuals to perform daily activities periodically or permanently [1][2][3][4] and makes it difficult for them to return to their occupation. 5,6 The musculoskeletal manifestations of arthropathy of the hands in patients with systemic lupus erythematosus include persistent pain, swelling, stiffness, decreases handgrip strength, and disability.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The musculoskeletal manifestations of arthropathy of the hands in patients with systemic lupus erythematosus include persistent pain, swelling, stiffness, decreases handgrip strength, and disability. 1,3,7 Restoration of normal hand function in patients with arthropathy of the hands is a goal that is necessarily subordinate to sustain life. Grasping and transporting objects are the frequently encountered tasks in the activities of daily livings, and its dysfunctions have a severe impact on the patient's normal life.…”
Section: Introductionmentioning
confidence: 99%